2021
DOI: 10.1186/s12888-021-03288-x
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of symptoms of body dysmorphic disorder (BDD) and associated features in Swiss military recruits: a self-report survey

Abstract: Background Body dysmorphic disorder (BDD), defined as the obsessive idea that some aspect of one’s own body or appearance is severely flawed/deformed, is relatively common in the general population and has been shown to have strong associations with mood and anxiety disorders and substance abuse disorders. Furthermore, a previous study on symptoms of BDD among people in the military showed that muscles are an important area of preoccupation. Hence, this study aimed to 1. assess the prevalence o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0
15

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(22 citation statements)
references
References 14 publications
(39 reference statements)
0
4
0
15
Order By: Relevance
“…Campagna and Bowsher 11 reported prevalence rates of BDD (13% in men, 22% in women, 18% in soldiers, 12% in sailors, 13% in airmen) and prevalence rates of MD (13% in men, 4% in women). Another study comprised of 126 male Swiss military recruits showed that symptoms of BDD were common, with 9.5% assessed for probable BDD and 84% reporting some symptoms of BDD 30…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Campagna and Bowsher 11 reported prevalence rates of BDD (13% in men, 22% in women, 18% in soldiers, 12% in sailors, 13% in airmen) and prevalence rates of MD (13% in men, 4% in women). Another study comprised of 126 male Swiss military recruits showed that symptoms of BDD were common, with 9.5% assessed for probable BDD and 84% reporting some symptoms of BDD 30…”
Section: Resultsmentioning
confidence: 99%
“…Regarding the branch of service, BDD seems to be more prevalent in soldiers (18%) than in sailors (12%) and airmen (13%). The prevalence of MD can be estimated to be ~15% in men and ~5% in women 4 8 11 30. These prevalence rates are much higher than those found in the normal population18–20 which indicates that BDD and MD are of particular relevance in military populations.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…De acordo com Brito et al (2021), trabalhos motivacionais realizados pelos profissionais de educação física e pelas academias de musculação podem contribuir para a manutenção do indivíduo nesse ambiente, acarretando menores índices de abandono.…”
Section: Fatores Que Motivam a Permanência Na Prática De Musculaçãounclassified
“…Em um estudo feito com adolescentes por Schneider e colaboradores(2019), foi observado que 44,1% dos participantes do sexo masculino demonstraram mais preocupação associando aos músculos. Isso os motivava a se entregar ao crescimento muscular, se baseando em estratégias de mudança corporal, com o uso de diferentes suplementos, dietas muitas vezes sem orientação profissional e a prática excessiva de atividade física.De acordo com Bashir e colaboradores(2021), dos 211 fisiculturistas avaliados em seu estudo, todos apresentaram algum grau de Dismorfia Muscular. Os participantes foram classificados da seguinte forma: prevalência de dismorfia muscular leve (13,7%), dismorfi muscular moderada (62%) e dismorfia muscular grave (23,7%) o que confirma a elevada preocupação com a aparência física em jovens, como relatado anteriormente com outros autores.Druger e colaboradores(2021), observaram em seu estudo que a principal área de preocupação dos avaliados que apresentavam sintomas de TDC, eram seus músculos e 84% da amostra estudada demonstrou os sintomas.…”
unclassified